TV aberta e mídias sociais: o engajamento da audiência interativa na construção de conteúdos televisivos - Odorico, Nayana Franklin (2016)
This academic work has the objective to understand the acting of the protagonist of cyberculture in Brazil, the user, as well as his relevance for the construction of television content. The interest in the scenario comes from the multiplication of mobile devices usage and social media, that allowed interactive subjects to have more access to information and share it at any time, generating a series of changes in their behavior and habits. That influenced the change of attitude of some TV programs which have begun to introduce content and themes to their programming influenced by the internet. The main problem of this research is connected to the questioning about which audience responds to the participation invitations performed by the open TV network and how it uses this feedback to generate content. It is noticed a territory constructed and groped by young people in a scenario of engagement, creating a new collaborative public space that boosts the capacity of articulation and action of users. The open TV network programming stimulates the usage of social media not only as a form of interaction, but also as a possibility to new branches of transmidia content. The financial interests of big TV broadcasters and companies stand in first plan, however the produced content constantly needs reformulation and freshness of new formats. The study is based on the work of important brazilian and international authors of communication area that contributed to reflection and construction of the theoretical basis of analysis, such as: Cannito and the challenges of TV in the digital age; Clay Shirky and the behavior of a new spectator and culture of participation; Eugenio Trivinho and relevant studies about glocal and cyberculture dromocracy; Henry Jenkins and convergences of current media and transmedia narrative; besides Thompson and the studies on the development of media. The corpus analysis focuses on the night programming of Rede Globo de Televisão (the soap opera Verdades Secretas and the reality show BBB16) during the second half of 2015 and the first half of 2016. The sistematic observation fell on both TV programs and individual behavior on Facebook and Twitter. To assist the empiric analysis of the corpus, sources of market and consumer research were used, as well as qualitative research carried out with users, which enhanced the final results of this work